An initial evaluation of newly proposed biomarker of zinc status in humans - linoleic acid: dihomo-γ-linolenic acid (LA:DGLA) ratio. (October 2016) - Knez, Marija; Stangoulis, James C.R.; Zec, Manja; Debeljak-Martacic, Jasmina; Pavlovic, Zoran; Gurinovic, Mirjana; Glibetic, Maria
Summary: Background: Zinc is an essential micronutrient for humans with important physiological functions. A sensitive and specific biomarker for assessing Zn status is still needed. Objective: The major aim of this study was to examine if the changes in the content of plasma phospholipid LA, DGLA and LA: DGLA ratio can be used to efficiently predict the dietary Zn intake and plasma Zn status of humans. Methods: The study was performed on healthy human volunteers, 25–55 years of age. The dietary Zn intake was assessed using 24 h recall questionnaires. Plasma phospholipid fatty acid analysis was done by gas chromatography, and plasma analysis of minerals by atomic absorption spectrometry. Biochemical, anthropometrical and hematological parameters were assessed. Results: No significant relationship was found between the dietary and plasma zinc status (r = 0.07; p = 0.6). There was a statistically significant correlation between DGLA and plasma Zn (r = 0.39, p = 0.00). No relationship was observed between the linoleic acid and plasma Zn, while there was a significant negative correlation between LA: DGLA ratio and plasma Zn status (r = −0.35, p = 0.01). Similarly, there were statistically significant difference in DGLA status (p = 0.004) and LA: DGLA ratio (p = 0.042) between the Zn formed groups. Conclusions: This study is an initial step in evaluating LA: DGLA ratio as a biomarker of Zn status in humans. The results are encouraging as they show that concentration of DGLA is decreased and LA: DGLA ratio increased in people with lower dietary Zn intake. However, additional studies are needed to fully examine the sensitivity of this biomarker.